PENGARUH SIKAP RELIGIUSITAS MAHASISWA TERHADAP PRESTASI BELAJAR - Pitaloka, Fasya Amalia; Linda Supriatin; Nabilah Azhar; Septy Qurratu Aini; Hisny Fajrussalam (Program Studi Akuntansi IKOPIN, 2022)
The attitude of one's student religiosity can be seen from various sides of human life. Religious activities are not only seen from perseverance in worship (rituals), but when carrying out other activities outside of worship that is driven by supernatural attitudes, it becomes one of the attitudes of religiosity. This attitude of religiosity is usually one of the factors of one's achievement. Through the understanding of each religion that is taught, it gives birth to good habits in its activities. This study habit will increase one's achievement in learning and attitude. To be able to prove it, it is necessary to do research on this problem. The purpose of this study is to determine the most dominant religious attitude towards learning achievement. This research was conducted using quantitative research with online questionnaire data collection to students and educators. The results show that most of the religious attitudes in the form of reading the Koran are the most dominant attitudes that affect learning achievement. They mentioned that the cultivation of religious attitudes in Islamic teachings can develop one's character, apart from that religious attitudes also have a positive role in one's learning outcomes. Although, a religious attitude does not guarantee a person's level of success, at least a good attitude is embedded in oneself.